KONTRIBUSI STATUS GIZI DAN TINGKAT KESEGARAN JASMANI TERHADAP HASIL BELAJAR PENJASORKES SISWA KELAS V SD NEGERI 048 BENGKALIS KABUPATEN BENGKALIS - M.Zulfadhli, M.Zulfadhli; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, problem in this study is the low learning outcomes of students in elementary school penjasorkes 048 Bengkalis Bengkalis. Many factors affect the penjasorkes learning outcomes, such as nutritional status and physical fitness. This study aims to determine the contribution of nutritional status and physical fitness of the students' learning outcomes penjasorkes Elementary School 048 Bengkalis Bengkalis. This type of research is correlational. The population in this study is the whole student Elementary School 048 Bengkalis Bengkalis numbering as many as 113 people. The sampling technique used purposive sampling. Thus the number of samples in this study are 23 male students. Data were collected by using a measurement of both variables. To measure nutritional status using anthropometric tests, and to measure physical fitness using TKJI. While the results obtained from the value of learning penjasorkes mid semester. Data were analyzed with Pearson product moment correlation and followed with a double. The data was analyzed by showing that the first hypothesis is a contribution of nutritional status on learning outcomes penjasorkes with a large contribution is 17.31%. The second hypothesis is a contribution to the learning outcomes of physical fitness penjasorkes with a large contribution is 18.49%. While the third hypothesis is a contribution of nutritional status and physical fitness together on learning outcomes penjasorkes with a large contribution is 31.02%.Keywords : nutritional status, level of physical fitness, learning outcomes penjasorkes